Stem Distributions and Height-Diameter Allometries for Two Species of Irvingiaceae (Exell And Mendonça) in a Tropical Moist Forest of Southern Nigeria (2013)
The study investigated stem distributions and height-diameter relationships of two Irvingiaceae species in Oban Forest, Cross River State, Nigeria with a view to suggesting appropriate management strategies for their conservation in the area. Using systematic sampling technique, six 2km-transect was cut in each of the primary and secondary forests in the area. Four 50m×50m plots were laid alternately along each transect. Thus, twenty-four plots were used in each of the two forest types, making a total of 48 sample plots for the study. On each of the sample plots, Irvingia wombulu and Klainedoxa gabonensis were identified and their growth parameters measured on the trees with DBH≥10cm. Data were analyzed using descriptive and inferential statistics. The result reveals that there were average of 3 and 4 I. wombulu and K. gabonensis stems/ha respectively in the area. About 47% of I. wombulu fell in the height class 10-20m, about 36% of K. gabonensis fell in the height class 21-30m. Both species have fewer stems in the height class of >40m. Tree diameter distributions reveal that about 33% of I. wombulu were in the class 10-39cm. Only 16% of K. gabonensis belong to this class. About 20% of K. gabonensis encountered fell in the diameter class ≥100cm. There were significant differences between most of the tree growth parameters for the two species. However, the species were found to exhibit similar growth patterns in the two forest types. All the height-diameter models presented in the study were significant. In all I. wombulu gave better models than the K. gabonensis, going by their modeling efficiencies and tests of bias. The models were therefore recommended for predictions in the study area